Principal's Leadership as An Educational Supervisor In Improving The Quality of Teaching and Learning - Ratna Sagala; Tubagus Pamungkas; Ramdhani Ramdhani (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to analyze the strategic role of the principal as an educational supervisor in improving the sustainable quality of teaching and learning at Tabgha Mulia School, Batam. The main focus is on implementing academic supervision through a collaborative and reflective leadership style. The study method used is a descriptive qualitative approach. Data were collected through in-depth interviews, direct observations, and document analysis. The data analysis technique used is the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results show that the principal’s leadership, which emphasizes collaboration, reflection, and mentoring, positively contributes to improving teacher professionalism, particularly in lesson planning, reflective thinking, and participation in quality development programs. However, several challenges were identified, including the lack of preparedness of instructional materials and unexamined teaching routines. It is concluded that effective academic supervision requires a substantive and contextual approach, along with the principal’s role as a facilitator in fostering an eval_uative culture within the school environment. The implication of this research highlights the importance of strengthening the principal’s capacity in conducting pedagogical supervision to achieve adaptive and sustainable teaching and learning quality